Improving Critical Thinking Skills and Learning Independence Using Problem Based Learning Based On Science Literation - Rubiyanti Rubiyanti; Badarudin Badarudin; Karma Iswasta Eka (Universitas Negeri Makassar, 2020)
The purpose of this study is to improve critical thinking skills and student learning independence using Problem Based Learning (PBL) models based on scientific literacy. The research used is PTK with 2 cycles and each cycle is carried out in 2 meetings, each meeting consisting of planning, action, observation, and reflection. The tools used to collect data are written test questions, observation sheets of teacher and student activities, observation sheets for learning independence attitude, questionnaire on learning independence attitude scale, and documentation. Subjects in this study were 28 students. The results showed that the first cycle students gained critical thinking skills with an average of 2.6 with enough categories, increased in cycle II to 3.6 with good categories. Learning independence in cycle I gained an average of 3.85 in the good category and increased in the second cycle to 3.9 in the good category. This proves that with PBL based on scientific literacy can improve critical thinking skills and independence of learning.